KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA: STUDI KASUS KAWASAN UNIT PENGELOLAAN PT. ADITUNGGAL MAHAJAYA, KABUPATEN SERUYAN, KALIMANTAN TENGAH - Harnios Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2011)
Ecosystems Degradation in the region of Aditunggal Mahajaya Ltd had caused the region to be functioning poorly as wildlife habitat. This was indicated by the low level of wildlife encounters, both on observations during this study as well as from interviews with some of the people who live in the area. In addition, other factors causing decline in wildlife populations was the high level of animal hunting. Most of the wildlife was found in a wooded area that had a relatively good canopy cover. This condition was found in the area around the river, and it was also found in the mix rubberwood forest areas owned by public administrations of Ayawan River Gardens (saye). There were 15 species of mammals, 17 species of birds and three species of reptiles found in the area which included in the rare/protected category from the total of 27 species of mammals, 54 species of birds, 6 species of reptiles found in the region. Keywords: ecosystem, habitat, wildlife, and diversity of wildlife species